Arabidopsis non-specific phospholipase C1: characterization and its involvement in response to heat stress - Krčková, Zuzana; Brouzdová, Jitka; Daněk, Michal; Kocourková, Daniela; Rainteau, Dominique; Ruelland, Eric; Valentová, Olga; Pejchar, Přemysl; Martinec, Jan (Frontiers in Plant Science, 2015)
The Arabidopsis non-specific phospholipase C (NPC) protein family is encoded by the genes NPC1 – NPC6. It has been shown that NPC4 and NPC5 possess phospholipase C activity; NPC3 has lysophosphatidic acid phosphatase activity. NPC3, 4 and 5 play roles in the responses to hormones and abiotic stresses. NPC1, 2 and 6 has not been studied functionally yet. We found that Arabidopsis NPC1 expressed in E. coli possesses phospholipase C activity in vitro. This protein was able to hydrolyse phosphatidylcholine to diacylglycerol. NPC1-green fluorescent protein was localized to secretory pathway compartments in Arabidopsis roots. In the knock out T-DNA insertion line NPC1 (npc1) basal thermotolerance was impaired compared with wild-type; npc1 exhibited significant decreases in survival rate and chlorophyll content at the seventh day after heat stress. Conversely, plants overexpressing NPC1 (NPC1-OE) were more resistant to heat stress compared with wild-type. These findings suggest that NPC1 is involved in the plant response to heat